Duodenal ileus from giant stone Bouveret syndrome - Ruso, Luis; Baldizán, Jorge; Lucinschi, Alicia; Sismondi, Adriana; Carriquiry, Luis; Praderi, Raúl (Cirugía del Uruguay, 1996)
Duodenal ileus due to biliar stones has the presenta/ion of a gastroduodena/ stenosis syndrome. lt was described by Bouveret in 1896. The authors report two cases with special features. In one of them, the clinica/ presentation of a voluminous tumor of the right hypochondrium made it impossible in the pre-operative to distinguish between a calcified hydatic cyst and a giant solitary stone. The other patient was diagnosed by means of fibrogastroscopy but the extraction tria/ of the stone failed. The literature review analyses the spectre of diagnostic and therapeutica/ possibilities. The importance of surgery as an integral curative procedure is pointed out; it is suggested that endoscopic extraction and eventual/y extracorporeal shock-wave lithotripsy should be reserved to patients with high surgico--anesthesical risk